2014
DOI: 10.3389/fncel.2014.00116
|View full text |Cite
|
Sign up to set email alerts
|

CSPα—chaperoning presynaptic proteins

Abstract: Synaptic transmission relies on precisely regulated and exceedingly fast protein-protein interactions that involve voltage-gated channels, the exocytosis/endocytosis machinery as well as signaling pathways. Although we have gained an ever more detailed picture of synaptic architecture much remains to be learned about how synapses are maintained. Synaptic chaperones are “folding catalysts” that preserve proteostasis by regulating protein conformation (and therefore protein function) and prevent unwanted protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…In addition, we created a plasmid for the expression of PA‐mCit‐tagged CSPα, a molecular chaperone in the synapse (Sharma et al , ). CSPα maintains protein homeostasis in the presynapse and likely associates with multiple proteins that play a role in synaptic transmission (Zhang et al , ; Donnelier & Braun, ). To this day, however, only a few direct binding partners such as SNAP25 or dynamin‐1 have been identified (Sharma et al , ; Zhang et al , ), suggesting that additional PPIs can be found by targeted interaction screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we created a plasmid for the expression of PA‐mCit‐tagged CSPα, a molecular chaperone in the synapse (Sharma et al , ). CSPα maintains protein homeostasis in the presynapse and likely associates with multiple proteins that play a role in synaptic transmission (Zhang et al , ; Donnelier & Braun, ). To this day, however, only a few direct binding partners such as SNAP25 or dynamin‐1 have been identified (Sharma et al , ; Zhang et al , ), suggesting that additional PPIs can be found by targeted interaction screening.…”
Section: Resultsmentioning
confidence: 99%
“…For validation and also upscaling, we performed targeted PPI screens with libraries of > 120 synaptic or non‐synaptic control proteins against the presynaptic chaperone CSPα (Donnelier & Braun, ). Identification of 42 synaptic proteins, with > 90% not yet described as CSPα partners, indicates that only few of the CSPα‐interacting proteins in the presynapse are currently known and confirms the protein's functional role in various synaptic processes (Südhof & Rizo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rab3 and CSP/Dnajc5 are the major protein components in a purified preparation of brain synaptic vesicles (Takamori et al . ; Donnelier & Braun ) and are located in the ribbon synapse (Uthaiah & Hudspeth, ). Rab3 attaches to synaptic vesicles through the C‐terminal geranyl‐geranyl moiety; cysteine‐string protein (CSP/Dnajc5) binds to synaptic vesicles through the palmitoyl residues of the cysteine strings near its centre and is a chaperone protein involved in rescue of unfolded synaptic proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Both cysteine string protein (CSP) and Fasciclin II (FasII) levels, however, were significantly affected in mib1 3 / mib1 EY09780 mutants. CSP, a vesicle-associated protein important for evoked neurotransmitter release (Bronk et al , 2005) and presynaptic protein folding (Donnelier & Braun, 2014), was significantly reduced at mib1 3 / mib1 EY09780 mutant NMJs (Fig. 7B).…”
Section: Resultsmentioning
confidence: 99%